Feeding Patterns of Healthy Term Newborns in the First 5 Days—The Glucose in Well Babies Study (GLOW). (November 2022) - Harris, Deborah L; Weston, Philip J; Harding, Jane E
Background: The feeding patterns of healthy newborns have been poorly described. Research Aim: To determine the feeding patterns of healthy term newborns soon after birth, and if these differed with sex, gestation, and mode of birth. Methods: This study was a prospective, longitudinal observational cohort study. Term, appropriately grown newborns ( N = 66) were fed according to maternal choice and details were recorded. Data were analyzed using generalized Poisson regression for feeding frequencies, and mixed model regression of log-transformed data for durations. Results: The participants completing the study had a M = 3589 g ( SD = 348 g) birthweight, with a gestation age of M = 40.1 (1.2) weeks. All participants were breastfed; 23 (35%) also received expressed human milk and 10 (15%) received formula. Participants had fewer feeding sessions on Day 1, ( M = 7.3 [1.9] sessions/day) increasing to ( M = 9.4 [2.4] sessions/day) by Day 3, then reducing to ( M = 9.0 [2.2] sessions/day) on Day 5, p < .001. The overall duration of breastfeeding sessions varied widely ( Mdn = 29 [range = 1–447] min). Feed frequency but not duration was higher in males than females ( M = 8.9, SE = 0.2 vs. 8.1, 02, sessions/day, p = .03), in newborns born ≥ 40 weeks' gestation ( M = 8.9, SE = 0.3 vs. 8.2, 02, sessions/day, p = .04), and in newborns born by Caesarean section ( M = 9.4, SE = 0.3 vs. 8.4, 02, sessions/day, for vaginal birth, p = .003). Conclusion: Feeding patterns of healthy term newborns vary widely, but frequency increases during the first 3 days, and is greater in males, newborns born late term, and born by Caesarean section. Clinical Trial Registration: The Australian and New Zealand Clinical Trials Registry Ref: ACTRN12615000986572. The study protocol is available online:http://hdl.handle.net/2292/32066